Role of NLRP3 Inflammasome in Lupus Nephritis and Therapeutic Targeting by Phytochemicals - Wu, Dantong; Ai, Lianjie; Sun, Yanping; Yang, Bingyou; Chen, Sisi; Wang, Qiuhong; Kuang, Haixue (Frontiers in Pharmacology, 2021)
Systemic lupus erythematosus (SLE) is a multisystem autoimmune inflammatory condition that affects multiple organs and provokes extensive and severe clinical manifestations. Lupus nephritis (LN) is one of the main clinical manifestations of SLE. It refers to the deposition of immune complexes in the glomeruli, which cause kidney inflammation. Although LN seriously affects prognosis and represents a key factor of disability and death in SLE patients, its mechanism remains unclear. The NACHT, leucine-rich repeat (LRR), and pyrin (PYD) domains-containing protein 3 (NLRP3) inflammasome regulates IL-1β and IL-18 secretion and gasdermin D-mediated pyroptosis and plays a key role in innate immunity. There is increasing evidence that aberrant activation of the NLRP3 inflammasome and downstream inflammatory pathways play an important part in the pathogenesis of multiple autoimmune diseases, including LN. This review summarizes research progress on the elucidation of NLRP3 activation, regulation, and recent clinical trials and experimental studies implicating the NLRP3 inflammasome in the pathophysiology of LN. Current treatments fail to provide durable remission and provoke several sides effects, mainly due to their broad immunosuppressive effects. Therefore, the identification of a safe and effective therapeutic approach for LN is of great significance. Phytochemicals are found in many herbs, fruits, and vegetables and are secondary metabolites of plants. Evidence suggests that phytochemicals have broad biological activities and have good prospects in a variety of diseases, including LN. Therefore, this review reports on current research evaluating phytochemicals for targeting NLRP3 inflammasome pathways in LN therapy.